2017
DOI: 10.1176/appi.ajp.2016.16030319
|View full text |Cite
|
Sign up to set email alerts
|

No Association of Lower Hippocampal Volume With Alzheimer’s Disease Pathology in Late-Life Depression

Abstract: Lower hippocampal volume was not related to amyloid pathology in this sample of patients with late-life depression. These data counter the common belief that changes in hippocampal volume in late-life depression are due to prodromal Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
54
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 39 publications
0
54
1
3
Order By: Relevance
“…However, studies have thus far been limited to amyloid PET [6, 7, 18]. Amyloid was not cross-sectionally associated with subclinical depressive symptoms in a cohort of cognitively normal elderly [6], and was not elevated in older adults with major depressive disorder relative to healthy controls [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies have thus far been limited to amyloid PET [6, 7, 18]. Amyloid was not cross-sectionally associated with subclinical depressive symptoms in a cohort of cognitively normal elderly [6], and was not elevated in older adults with major depressive disorder relative to healthy controls [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have thus far been limited to amyloid PET [6, 7, 18]. Amyloid was not cross-sectionally associated with subclinical depressive symptoms in a cohort of cognitively normal elderly [6], and was not elevated in older adults with major depressive disorder relative to healthy controls [18]. In contrast, studies by Lavretsky, Kumar and colleagues have shown associations between depressive symptoms in CN, MCI, and late life depression subjects and retention of a PET ligand thought to bind both amyloid and tau [19, 20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is highlighted by the study’s secondary analyses, where there was no difference in amyloid binding observed between early-onset and late-onset depressed subjects (1). Supporting these findings, some previous studies in both cognitively impaired and cognitively intact older adults have similarly failed to associate amyloid burden with depressive symptoms (7; 8).…”
mentioning
confidence: 96%
“…De Winter and colleagues (1) prospectively examined 48 depressed older adults and 52 age- and sex-matched comparison subjects. Participants in this cross-sectional study completed [ 18 F] flutemetamol amyloid positron emission tomography, structural MRI for measurement of hippocampal volume, apolipoprotein E genotyping, and neuropsychological assessments.…”
mentioning
confidence: 99%